From dead street to a vibrant street determining the vibrancy of Escolta, Manila for laying out future revitalization plans - Ticao, Mar Lorence G. (Quezon City College of Architecture, University of the Philippines Diliman, 2012)
Manila City contains Metro Manila's old business districts. Today, Manila shares the plight of most old city cores, driven toward decline, and even facing the crisis of losing their original character and cultural significance in efforts to keep up with recent urban developments. Most streets in Manila have strategic locations that were major contributors to its economic and social vibrancy. These streets can still play important roles in contributing to manila's development, banking on their historic value and location, for business and tourism opportunities. Escolta, one of the most important historic business districts in Manila, considered as a dead street by most, has both. This study was conducted to determine key areas in Escolta which can possibly help strengthen its vibrancy and identify issues and problems that should be addressed. The study can serve as a spring board for identifying areas to focus on for the revitalization of Escolta.
Vita.
Thesis (Master of Architecture)--University of the Philippines Diliman.
Keywords: Urban renewal -- ManilaCity -- Escolta; Central business districts -- Manila City -- Escolta; City planning -- Manila City -- Escolta; Escolta (Manila).